Linking Future Time Perspective to Career Maturity: The Mediating Role of Self Efficacy - Khairani Zikrinawati; Aisyah (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2026)
Career maturity is a condition when an individual already has a view, preparation, and confidence in themselves in facing the professional world of work. Career maturity is a crucial thing that a student must have in order to facilitate achieving relevant work after graduating from college. This study aims to empirically test the effect of future time perspective on career maturity, with self-efficacy as a mediator on university students population. The results of the study showed that future time perspective has a direct and significant effect on career maturity (p <0.05). Self-efficacy was also proven to mediate the effect of future time perspective on career maturity (p <0.05). This shows that self-efficacy only partially mediates the relationship between future time perspective and career maturity, and there are still other variables that can fully mediate the relationship between the two, but were not examined in this study.